The commodification of women's empowerment: The case of Vagina Varsity. (December 2019) - Roux, Shanleigh; Peck, Amiena
Abstract: Vagina Varsity is a South African online campaign aimed at selling Libresse sanitary products to ostensibly young women in South Africa, primarily through the medium of YouTube. In this paper, we investigate the privileging of white women's bodies over those of women of colour in the campaign. In so doing, we tease out how patriarchy is multi-layered and experienced differently by women depending on their race and class. Moreover, we see that black South African women's issues are being served by the campaign only to the extent which they coincide with those of the dominant group, i.e. white women in South Africa. To critically investigate this phenomenon, we use an intersectionality framework (Crenshaw, 1989) to discern latent differences in the treatment of black and white women's bodies in the campaign. Multimodality (Kress, 2010; Iedema, 2003) allows us to analyse texts, sounds and images used in the campaign. Importantly, however, we also adopt Kulick's (2003) notion of 'dual indexicality' to explore what is absent or silent in the campaign. We argue that the model of capitalism which commodifies women's empowerment serves to multimodally exclude black women's lived experience of patriarchy and pain.